Potensial Antibakteri Dari Tanaman Suku Anak Dalam (SAD) di Provinsi Jambi - Lestari, Uce; Nalinda, Elba Annisa; Fitri, Khairunnisa Rizkia (LPPM Universitas Sari Mulia, 2025)
Background: Bacterial infection is an event that is always a problem in the world of health. Bacterial infection can cause diseases such as diarrhea where the vector of transmission can be through the hands. Prevention can be done by maintaining hand hygiene, one of which is by using topical preparations that provide antibacterial activity made from natural ingredients, especially natural ingredients that are used by the Anak Dalam Tribe (SAD) in Jambi Province as medicine. Objective: To find out the potential of plants used by the Anak Dalam tribe in Jambi Province as antibacterials. Method: This study uses a systematic review method of the PRISMA method by searching for scientific publications in 2015-2025 based on the Crossref database. Results: The results obtained were endemic plants used by the Suku Anak Dalam (SAD) as medicine that have antibacterial activity against gram-positive and gram-negative bacteria such as S. aureus and E. Coli Conclusion: Plants that are often used by the Suku Anak Dalam as medicines have antibacterial abilities so that it can be proven that these plants have scientific evidence as antibacterials